2005
DOI: 10.1177/0269881106063266
|View full text |Cite
|
Sign up to set email alerts
|

Memory function and serotonin transporter promoter gene polymorphism in ecstasy (MDMA) users

Abstract: Although 3,4-methylenedioxymethamphetamine (MDMA or ecstasy) has been shown to damage brain serotonin (5-HT) neurons in animals and possibly humans, little is known about the long-term consequences of MDMA-induced 5-HT neurotoxic lesions on functions in which 5-HT is involved, such as cognitive function. Because 5-HT transporters play a key element in the regulation of synaptic 5-HT transmission it may be important to control for the potential covariance effect of a polymorphism in the 5-HT transporter promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
4
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 62 publications
2
47
4
2
Order By: Relevance
“…However, in a subsequent study in which ecstasy users were found to be impaired in various aspects of memory performance, female users were not significantly more affected than male users (Reneman et al, 2006). It is also worthy of note that the gender-drug use interaction only emerged on event based PM tasks and not on the time based PM measure.…”
Section: Discussionmentioning
confidence: 84%
“…However, in a subsequent study in which ecstasy users were found to be impaired in various aspects of memory performance, female users were not significantly more affected than male users (Reneman et al, 2006). It is also worthy of note that the gender-drug use interaction only emerged on event based PM tasks and not on the time based PM measure.…”
Section: Discussionmentioning
confidence: 84%
“…A polymorphism in the 5-HT transporter promoter gene region that has been shown to regulate transporter densities in human cell lines [77] might be one such predisposing factor. Indeed, many studies have attempted to relate this polymorphism with drug abuse [78][79][80] . In 1 trial, cognitive deficits in MDMA abusers were not explained by this polymorphism, but there are no studies that have examined the role in the propensity to abuse MDMA [79] .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, many studies have attempted to relate this polymorphism with drug abuse [78][79][80] . In 1 trial, cognitive deficits in MDMA abusers were not explained by this polymorphism, but there are no studies that have examined the role in the propensity to abuse MDMA [79] . These are difficult studies to conduct in humans, but animal research would be very useful, since the acquisition and maintenance of self-administration can be easily measured in the laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…Where no ecstasy-related WCST performance deficits were reported other drug consumption was controlled through the use of 1 or more matched control groups [26][27][28][29] . In 1 study results on the dependent variables analysed were not reported in detail [26] .…”
Section: Ecstasy and Executive Shiftingmentioning
confidence: 99%